If it's not what You are looking for type in the equation solver your own equation and let us solve it.
+6=5/4T
We move all terms to the left:
+6-(5/4T)=0
Domain of the equation: 4T)!=0We add all the numbers together, and all the variables
T!=0/1
T!=0
T∈R
-(+5/4T)+6=0
We get rid of parentheses
-5/4T+6=0
We multiply all the terms by the denominator
6*4T-5=0
Wy multiply elements
24T-5=0
We move all terms containing T to the left, all other terms to the right
24T=5
T=5/24
T=5/24
| 1.290=h/10=h/5 | | 4x+3=2x+12-3x | | 11x+8=3x+12 | | 8+x/3=-7x3=-21 | | F(-8)=6x-3 | | -7-7(x-6)=35+x | | -3n=3(-8-2n) | | 8(2x-4)=12+6x | | 5-6(6n-2)=233 | | 6x+8=15x-3 | | H=-16t^2+124t+32 | | H=1024-16t^2 | | 4x^2+-5x+-12=0 | | 20x^2-48x-48=0 | | 20x^2-48x48=0 | | 10x+4-2x=8+3x | | 5x-2x=4-5 | | g(6)=1 | | -2(b-18)=16 | | 5(x-1)=(x-2) | | 7x+25=64 | | 3(-4b)+40/2=-4b | | F(x)=2/5x-12 | | 9+2=(-6j)+7 | | 4x+6+55=180 | | 4=10x=31+x | | -(r+6)=-14 | | 3d+5d=3 | | -7j-14j+9=12 | | x+7+3x=43 | | 2m+9+m=33 | | 2m+9+m=m |